Analysis of challenges in managing and developing of contemporary waqf in the federal territory, Malaysia - Saiman, Muhamad Zuhaili bin; Ruzaidi, Wan Norelliyana bt (International Journal of Asian Social Science, 2024)
The purpose of the study was to analyze and find out the issues in managing and developing contemporary waqf practices in current practice in the Federal Territories, Malaysia. The Federal Territory was used as a sample for this study because it is the capital of the country which is the focus of development and modernization from various aspects including contemporary waqf. This study used the qualitative design in research method which is data collection is through primary sources by interview conducted with Islamic Religious Council of the Federal Territory (IRCFT) at Zakat Collection Center (ZCC) officials from the Waqf Unit who were also former project managers at the IRCFT’s Waqf Center. The findings shows the contremporary waqf is a type of charity that has special characteristics compared to other charitable activities. In fact, therea are three differ in their specific practice contexts and objectives. This contemporary waqf is very important because it will maximize the accumulated waqf funds in addition to developing a more modern ummah economy in accordance with current benefit. The practical implications, the data for this study is very important to assist authorities such as the Islamic Religious Council of the Federal Territory (IRCFT) in planning promotions to open the minds of the community, especially Muslims, regarding the wider importance and effectiveness of contemporary waqf that is in line with the changing times to meet the current needs of the community and the country.